1990
DOI: 10.1902/jop.1990.61.12.732
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of a Biodegradable Collagen Membrane in Guided Tissue Regeneration

Abstract: A bio-resorbable type I collagen membrane was investigated as a barrier for guided tissue regeneration. Ten human subjects with at least one pair of contralateral periodontal lesions with probing pocket depths of greater than or equal to 5 mm and radiographic evidence of greater than or equal to 40% bone loss were included. Each patient underwent contralateral surgical flap procedures. A collagen barrier was adapted to the tooth in the experimental defect and the flap replaced and sutured. The controls consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(73 citation statements)
references
References 10 publications
(2 reference statements)
1
71
0
1
Order By: Relevance
“…[1][2][3] A variety of applications of collagen has been reported to some diseases involving wound dressing, 4 peripheral nerve growth support, 5 and guided tissue regeneration for periodontal diseases. 6 We have attempted to regenerate the periodontal ligament (PDL) around dental titanium implants through PDL cell culture on collagen-immobilized implant [titanium + poly(ethylene-co-vinyl alcohol) (EVA) + collagen]. EVA has a high affinity with titanium and is so bioinert as to be applied to blood materials such as filter and permeability membranes.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] A variety of applications of collagen has been reported to some diseases involving wound dressing, 4 peripheral nerve growth support, 5 and guided tissue regeneration for periodontal diseases. 6 We have attempted to regenerate the periodontal ligament (PDL) around dental titanium implants through PDL cell culture on collagen-immobilized implant [titanium + poly(ethylene-co-vinyl alcohol) (EVA) + collagen]. EVA has a high affinity with titanium and is so bioinert as to be applied to blood materials such as filter and permeability membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies (Pitaru, 1987(Pitaru, , 1989YafTe, 1987) reported utilizing various forms of type I collagen as a membrane barrier for guided tissue regeneration procedures. Clinical human studies (Chung et al, 1990;Anderson, 1991) have also demonstrated positive results with type I collagen membranes in the treatment of periodontal defects using guided tissue regeneration techniques. Mendieta and Williams (1994) highlighted in their review the potential of crosslinked type I collagen together with polylactic acid as a suitable absorbable membrane.…”
Section: Extracellular Matrix In Clinical Applicationmentioning
confidence: 99%
“…Studies investigating commonly used techniques for tissue regeneration, including guided bone regeneration (GBR) and guided tissue regeneration (GTR), have emphasized the need for barrier membranes to prevent the apical growth of unwanted cells (epithelium and gingival connective tissue) within the wound area and maintain space for an adequate period during the early healing phase [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%